Math. - Freeland, Sherry (Education Digest, 1985)
The article focuses on a new report of the National Council of Teachers of Mathematics on the effects of technology on math instruction, which says that elementary school students should have calculators available to them as a matter of course, including during tests. Technology is changing things, it said, and calculators and computers should be used from students' first experiences with math. To accommodate technology, elementary school math should stress the meaning of arithmetic functions more than simple facts. Elementary school students should learn simple computer programming and be able to write fairly sophisticated programs by grade 6, the report said. In the middle school, according to the math teachers, technology should be used to teach nontraditional methods of problem solving and to display graphics for geometry.